Computer Vision and Graphics International Conference, ICCVG 2010, Warsaw, Poland, September 20-22, 2010, Proceedings, Part II - Bolc, Leonard; Tadeusiewicz, Ryszard; Chmielewski, Leszek J.; Wojciechowski, Konrad; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book is part II of a two-volume work that contains the refereed proceedings of the International Conference on Computer Vision and Graphics, ICCVG 2010, held in Warsaw, Poland, in September 2010. The 95 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in three topical sections: advances in pattern recognition, machine vision and image understanding; human motion analysis and synthesis; and computer vision and graphics.
Computer Vision and Graphics -- A Constraint Satisfaction Framework with Bayesian Inference for Model-Based Object Recognition -- Visual Programming Environment Based on Hypergraph Representations -- MRI Brain Segmentation Using Cellular Automaton Approach -- Improved Context-Based Adaptive Binary Arithmetic Coding in MPEG-4 AVC/H.264 Video Codec -- Local Polynomial Approximation for Unsupervised Segmentation of Endoscopic Images -- A Proper Choice of Vertices for Triangulation Representation of Digital Images -- A Method for Novel Face View Synthesis Using Stereo Vision -- Outer Surface Reconstruction for 3D Fractured Objects -- Application of the FraDIA Vision Framework for Robotic Purposes -- Video Analysis Based on Mutual Information -- Speeding Up Powerful State-of-the-Art Restoration Methods with Modern Graphics Processors -- Multi-layered Framebuffer Condensation: The l-buffer Concept -- Accurate Overlap Area Detection Using a Histogram and Multiple Closest Points -- Automatic Extraction of the Lower Boundary of the Mandibular Bone in Dental Panoramic Radiographs -- Football Player Detection in Video Broadcast -- Spectrum Evaluation on Multispectral Images by Machine Learning Techniques -- Fatigue Detector Using Eyelid Blinking and Mouth Yawning -- Inferior Maxillary Bone Tissue Classification in 3D CT Images -- Vector Median Splatting for Image Based Rendering -- Feature Extraction Using Reconfigurable Hardware -- Automated Counting and Characterization of Dirt Particles in Pulp -- Keypoint-Based Detection of Near-Duplicate Image Fragments Using Image Geometry and Topology -- Three Cameras Method of Light Sources Extraction in Augmented Reality -- The Context-Sensitive Grammar for Vehicle Movement Description -- The Method for Verifying Correctness of the Shape$1 (Bs Changes Calculation in the Melting Block of Ice -- A Real Time Vehicle Detection Algorithm for Vision-Based Sensors -- Sequential Reduction Algorithm for Nearest Neighbor Rule -- GPU-Supported Object Tracking Using Adaptive Appearance Models and Particle Swarm Optimization -- GFT: GPU Fast Triangulation of 3D Points -- Methods for Visualization of Bone Tissue in the Proximity of Implants -- An Evaluation of Image Feature Detectors and Descriptors for Robot Navigation -- The Visual SLAM System for a Hexapod Robot -- Displacement Calculation of Heart Walls in ECG Sequences Using Level Set Segmentation and B-Spline Free Form Deformations -- Fast and Accurate Machined Surface Rendering Using an Octree Model -- PATSI $1 (BPhoto Annotation through Finding Similar Images with Multivariate Gaussian Models -- Generation of Temporally Consistent Depth Maps Using Nosie Removal from Video -- Smooth Detail Features on Multiresolution Surface -- Using Parallel Graph Transformations in Design Support System -- Fast, Parallel Watershed Algorithm Based on Path Tracing -- Detection of Tumor Tissue Based on the Multispectral Imaging -- A New Method for ECG Signal Feature Extraction -- Error Concealment Method Selection in Texture Images Using Advanced Local Binary Patterns Classifier -- Early Warning System for Air Traffic Control Using Kinetic Delaunay Triangulation -- GPU Calculated Camera Collisions Detection within a Dynamic Environment -- Utilization of Multi-spectral Images in Photodynamic Diagnosis -- The Spectral Analysis of Human Skin Tissue Using Multi-spectral Images -- Can the Coronary Artery Centerline Extraction in Computed Tomography Images Be Improved by Use of a Partial Volume Model?.s
Keywords: Computer science; Computer software; Artificial intelligence; Computer vision; Computer graphics; Optical pattern recognition; Computer Science; Image Processing and Computer Vision; Computer Imaging, Vision, Pattern Recognition and Graphics; Artificial Intelligence (incl. Robotics).; Computer Graphics; Pattern Recognition; Algorithm Analysis and Problem Complexity